Maximizing the Impact of Community-Based Practitioners in the Quest for Universal Health Coverage - Campbell, James; Admasu, Kesetebirhan; Soucat, Agnes; Tlou, Sheila (World Health Organization, 2015)
The last decade has highlighted major gaps in the availability, accessibility, acceptability and quality of the health workforce in many countries. The quantity, skills and geographic distribution of the health workforce have long been recognized as factors that limit population health outcomes and progress towards the related Millennium Development Goals. Similarly, the even more ambitious health targets included in the Sustainable Development Goals – scheduled for adoption by the United Nations General Assembly later this month – may be undermined by the same factors.